2016
DOI: 10.3390/nu8120814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Proteins on the Uptake, Distribution, and Excretion of Phenolics in the Human Body

Abstract: Polyphenols, a complex group of secondary plant metabolites, including flavonoids and phenolic acids, have been studied in depth for their health-related benefits. The activity of polyphenols may, however, be hampered when consumed together with protein-rich food products, due to the interaction between polyphenols and proteins. To that end we have tested the bioavailability of representatives of a range of polyphenol classes when consumed for five days in different beverage matrices. In a placebo-controlled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
0
14
0
2
Order By: Relevance
“…One possible explanation is that with increasing age, the number of beneficial microorganisms in the colon decrease [42], which is likely to include those involved in flavonoid metabolism, and could potentially explain any delay in absorption in the current study considering the population tested. Furthermore, the intervention powders were suspended in milk and whilst some research such as that of Draijer et al [43] suggests that dairy proteins do not affect the bioavailability of polyphenols, there is also evidence to the contrary, with a study by Xiao et al [44] reporting that consuming milk with anthocyanins can affect their absorption. Overall, this suggests that the 5 hour post drink timepoint in the current study could have been too early to capture the maximum cognitive benefit that may otherwise have been evident following the acute anthocyanin-rich blueberry intervention.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that with increasing age, the number of beneficial microorganisms in the colon decrease [42], which is likely to include those involved in flavonoid metabolism, and could potentially explain any delay in absorption in the current study considering the population tested. Furthermore, the intervention powders were suspended in milk and whilst some research such as that of Draijer et al [43] suggests that dairy proteins do not affect the bioavailability of polyphenols, there is also evidence to the contrary, with a study by Xiao et al [44] reporting that consuming milk with anthocyanins can affect their absorption. Overall, this suggests that the 5 hour post drink timepoint in the current study could have been too early to capture the maximum cognitive benefit that may otherwise have been evident following the acute anthocyanin-rich blueberry intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent investigations on the bioavailability of anthocyanins and flavanones suggest that they could be more bioavailable than previously thought (Kay and others ). Data also show that protein‐rich diets do not influence the uptake, distribution, and excretion of phenols (Draijer and others ).…”
Section: Health Effects Of Plant Phenolic Compoundsmentioning
confidence: 91%
“…Furthermore, a study with 36 healthy males ingesting capsules containing 800 mg polyphenols with protein-rich dairy, soy, fruit-flavored drinks, or water, showed that the intake of polyphenols incorporated in protein-rich drinks did not change significantly the bioavailability of polyphenols or their metabolites [37].…”
Section: Bioavailability and Pharmacokinetics Of Resveratrolmentioning
confidence: 99%